Development Of Discovery Learning Based Interactive Learning MediaTo Improve Students' Problem Solving Skills And Mathematical Disposition Al-Ulum Islamic Junior High School Integrated Medan - Ramadhani, Nadya; Armanto, Dian; Mulyono, Mulyono (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2025)
This study aims to develop and analyze the validity, practicality, and effectiveness of Interactive Learning Media Based on Discovery Learning in enhancing students' problem solving skills and mathematical disposition. This research employs the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, and  Evaluation) development model. The learning media is developed in a digital format accessible via mobile devices or laptops and is designed interactively with an attractive interface, vibrant colors, and supplemented with audio and video learning materials. The Discovery Learning model implemented in this media consists of six main steps, namely stimulation, problem statement, data collection, data processing, verification, and generalization. Data collection techniques in this study included expert validation questionnaires, practicality questionnaires for students and teachers, as well as pretest and posttest assessments. The findings indicate that this Interactive Learning Media Based on Discovery Learning is highly valid, with an average validation score of 90.5% from subject matter experts, media experts, and design experts. Furthermore, this media achieved a practicality score of 86.72%, demonstrating that it is highly practical and easy to use by both students and teachers in the learning process. In terms of effectiveness, the posttest results show a significant improvement, with an average posttest score of 90% compared to the pretest score of 45.8%, confirming that this media is highly effective in enhancing students' understanding and problem-solving skills. Thus, based on validation results, practicality tests, and effectiveness evaluations, it can be concluded that the Interactive Learning Media Based on Discovery Learning has been proven to be valid, practical, and effective for use in mathematics learning, particularly in Systems of Linear Equations in Two Variables (SPLDV) for eighth-grade students at SMP Islam Al-Ulum Terpadu Medan. This media is expected to serve as an innovative alternative for improving the quality of mathematics learning and can be implemented more widely in various schools to support technology-based learning.